An Empirical Study on How IT Companies in Bangalore Collaborate with Educational Institutions to Develop Sustainability-Focused Curriculum on Employee Training and Development for Future IT Professionals - Smitha, Candida; Mani, S.; Arumugam, A. (Indian Journal of Information Sources and Services, 2025)
The paper was aimed at studying the collaboration of IT industry in Bangalore with educational institutions to prepare employee training (Develop sustainability focused curriculums). It is a quantitative, descriptive type of research through which we intend to observe the impact and feasibility of these partnerships for etching skills into new IT professionals. The data was collected through a questionnaire of 100 respondents which were HR managers, learning and development department from IT companies & faculty members of educational institutions that is analyzed by various statistical tools like chi-square test, correlation analysis & regression analysis. Our findings suggest substantial benefits of collaboration, but caution that it has limited effectiveness in delivering sustainability outcomes: there is a weak relationship between the extent to which collaborations are effective and their success at achieving sustainability outcomes. Proof of the fact that these variables are not directly related can be found in regression analysis. The study revealed significant barriers to ideal structural integration, such as insufficient resources and expertise. Through these findings, recommendations are developed to improve collaboration between institutions of learning and industry while ensuring that educational curricula meet the sustainable demands for possible development. This paper, therefore, recommends that the government implements more stringent policies supporting IT sustainability and constructs educational programs to focus on sustainable education for better job opportunities among IT professionals. This is also essential in preparing our environment against future challenges as well before it becomes too late.